2011
DOI: 10.2214/ajr.10.4577
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Evidence-Based Guidelines for Thyroid Nodule Biopsy: A Model for Establishment of Practice Standards

Abstract: Our study illustrates a method to evaluate the standard of practice for thyroid nodule assessment among radiologists within an ultrasound group. Application of a 5-point malignancy rating scale to select nodules for biopsy is feasible and shows good diagnostic accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
45
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 27 publications
7
45
1
Order By: Relevance
“…Regarding reproducibility, Hambly et al (24) studied the interobserver agreement of a five-point malignancy rating scale very similar to the TI-RADS score on 101 nodules. The interobserver agreement on whether to proceed to biopsy was fair to substantial, ranging from a k value of 0.38-0.69.…”
Section: Enhance Interobserver Agreementmentioning
confidence: 99%
“…Regarding reproducibility, Hambly et al (24) studied the interobserver agreement of a five-point malignancy rating scale very similar to the TI-RADS score on 101 nodules. The interobserver agreement on whether to proceed to biopsy was fair to substantial, ranging from a k value of 0.38-0.69.…”
Section: Enhance Interobserver Agreementmentioning
confidence: 99%
“…Thyroid ultrasonography is an extremely sensitive tool for the diagnosis of thyroid nodules and may be specific in diagnosing papillary thyroid cancer (Cesur et al 2006, Hambly et al 2011. Moreover, this imaging modality aids the decision-making processes of which nodules to target for fine needle aspiration biopsy (FNAB) and increases the diagnostic yield of thyroid cell sampling (Perros et al 2014, American Cancer Society 2015, Pitoia & Miyauchi 2015.…”
Section: Current Diagnostic Approaches and Limitationsmentioning
confidence: 99%
“…Moreover, this imaging modality aids the decision-making processes of which nodules to target for fine needle aspiration biopsy (FNAB) and increases the diagnostic yield of thyroid cell sampling (Perros et al 2014, American Cancer Society 2015, Pitoia & Miyauchi 2015. Multiple studies have confirmed typical sonographic features associated with increased risks of (Table 2) (Frates et al 2005, Hambly et al 2011, Lee et al 2011, and current guidelines now recommend the use of a combination of these features in algorithms predicting the likelihood of thyroid malignancy as well as the selection of nodules requiring FNAB (Perros et al 2014, Haugen et al 2015, Pitoia & Miyauchi 2015. Highresolution ultrasonography by an experienced operator is highly recommended in the initial evaluation of patients with thyroid nodules.…”
Section: Current Diagnostic Approaches and Limitationsmentioning
confidence: 99%
“…Third, previously suggested malignant US features may have different predictive values for malignancy depending on nodule characteristics such as echogenicity, which has not been clarified. Although several studies [13][14][15][16][17][18][19] have suggested scoring or categorization systems for malignancy risk, this is not firmly established, and some of the suggested systems are fairly complicated and less reproducible in clinical practice. Therefore, there is still a need to establish a reliable and practical US-based risk stratification system for thyroid malignancy.…”
Section: Introductionmentioning
confidence: 99%